Implementasi Sistem Jaringan Network Gateway dengan Portal Login Berbasis Web yang User-Friendly untuk Tenaga Pendidik di SMK Islamiyah Serua - Hidayatullah Al Islami; Jhodie Naufal Kertoprodjo; Afriaty Rohmah; Alya Salsabila Az Zahra; Brema Richardo Icwan Sembiring; Fathan Fatahillah; Gerald Andrew Manjatri; Hildan Wijianto; Muhammad Sholahuddin Al Ayubi; Tri Prasetyo; Yusup Septiana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This community service activity was carried out to overcome the problem of open and uncontrolled internet networks at SMK Islamiyah Serua. This condition poses security risks as well as inefficient bandwidth usage. The solution offered is the implementation of a network gateway system with a user-friendly web-based login portal, so that internet access can be limited only to educators through an authentication mechanism. The implementation method includes needs analysis, system design, implementation using MikroTik RouterOS and HTML/CSS/JavaScript-based web portals, system trials, and socialization to schools. The results showed a significant improvement in network security, bandwidth usage efficiency, and ease of access for teachers. In addition, this activity also increases educators' understanding of the importance of network security in supporting the learning process. The implementation of this system provides sustainable benefits for schools, both from a technical and educational perspective, because it is able to create a safer and more controlled digital environment. Thus, this community service activity not only solves technical problems, but also contributes to improving the quality of educational services at SMK Islamiyah Serua.